Analisis Efektivitas dan Kontribusi Penerimaan PBB-P2 pada Pendapatan Asli Daerah di Kota Gorontalo - Yusuf, Sriwahyuning; Hartati Tuli; Muliyani Mahmud (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aimed to determine the level of effectiveness and contribution of the Land and Rural and Urban Buildings Tax (PBB-P2) acceptance on the Local Revenue of Gorontalo City. The research method used in this study was a descriptive quantitative method. The data source for this research was primary data obtained directly from the Finance Agency of Gorontalo City in the form of interview results and Budget Realization Reports for 2018-2022. The results of this research indicated that the average effectiveness of achieving the PBB-P2 target acceptance was 89.76%, with the interpretation criterion being effective, even though the actual realization value generally had not been able to reach the set target. The significant average value of PBB-P2 acceptance effectiveness was due to the fact that in 2022, the actual acceptance realization exceeded 100% of the set target. Meanwhile, the contribution of PBB-P2 acceptance on the Local Revenue in Gorontalo City from 2018 to 2022 experienced fluctuations or ups and downs each year, with an average percentage acquisition of 3.58% and the interpretation criterion being Very Low.